Alzheimer's Disease Neuropathological Comorbidities are Common in the Younger-Old - Beach, Thomas G; Malek-Ahmadi, Michael (Journal of Alzheimer's disease, 2021)
Clinicopathological studies have demonstrated that Alzheimer's disease dementia (ADD) is often accompanied by clinically undetectable comorbid neurodegenerative and cerebrovascular disease that alter the rate of cognitive decline. Aside from causing increased variability in clinical response, it is possible that the major ADD comorbidities may not respond to ADD-specific molecular therapeutics. As most reports have focused on comorbidity in the oldest-old, its extent in younger age groups that are more likely to be involved in clinical trials is largely unknown; our objective is to provide this information. We conducted a survey of neuropathological comorbidities in sporadic ADD using data from the US National Alzheimer's Coordinating Center. Subject data was restricted to those with dementia and meeting National Institute on Aging-Alzheimer's Association intermediate or high AD Neuropathological Change levels, excluding those with known autosomal dominant AD-related mutations. Highly prevalent ADD comorbidities are not restricted to the oldest-old but are common even in early-onset ADD. The percentage of cases with ADD as the sole major neuropathological diagnosis is highest in the under-60 group, where "pure" ADD cases are still in the minority at 44%. After this AD as a sole major pathology in ADD declines to roughly 20%in the 70s and beyond. Lewy body disease is the most common comorbidity at younger ages but actually is less common at later ages, while for most others, their prevalence increases with age. Alzheimer's disease neuropathological comorbidities are highly prevalent even in the younger-old.